PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM MATERI KHALIFAH UMAR BIN KHATAB - Ramiati, Eka; Afandi, Ni’am; Fatimah, Nurul (INCARE, International Journal of Educational Resources, 2023)
This research aims to improve and produce comic learning media development products in the subject of Islamic Cultural History material Khalifa Umar bin Khattab, knowing the learning outcomes of students before and after using comic learning media development products. This development uses the Borg & Gall model which is adapted into 8 stages, namely (1) Research and data collection, (2) Planning, (3) Preparation of development media, (4) Expert vasility test, (5) Product revision, (6) Field trials, (7) Product revision after conducting product trials, (8) Dissemination and implementation. Research results obtained to determine the steps of development research are: Potential Problems, Data Collection and Needs Analysis, Product Design, Design Validation: Media Expert Test and Material Expert Test, Product Revision, Product Trial: User Test (Teacher), Individual, Small Group, Product Revision, Field Trial (student), Product Revision and Final result of Smart Apps Creator learning media packaged Android application. Based on calculations, pre-test and post-test values with N = 25 obtained a Mean of 57.2 obtained a Mean of 57.2 with Std. Deviation 11.37 and Std. Error Mean 2.27. Then the Post-test value with N = 25 obtained a Mean of 81.6 with Std. Deviation 11.06d and Std. Error Mean 2.21. Based on the results of the t test above, a Sig (2-tailed) value of 0.000<0.05 is obtained, then Ho and Ha are accepted. So the difference in influence is significant between pre-test and post-test results. Based on the exposure to the data above, it can be seen that comic learning media is effectively used in learning Islamic Cultural History subjects material for Caliph Umar bin Khattab Class V MI Assunniyyah Bagorejo.